examine and evaluate relationship between the positive leadership and its dimensions with teachers psychological capital - kamran sheivandi (Allameh Tabataba'i University Press, 2016)
The aim of this study is "examine and evaluate relationship between the positive leadership strategies with teachers psychological capital". For this purpose The study population consisted of all elementary school teachers in 2 City of tehran htat academic year 94-95 have been teaching,that 270 samples were selected according to a formula Krejcie and Morgan. Then the data were collected through the two questionnaires. The research method was descriptive - Survey and were investigated by using correlational and structural equation modeling. The findings from this study indicate that there is significant and positive relationship between positive leadership and its dimensions with psychological capital in the schools. The results also is indicate influence positive leadership on the psychological capital in among teachers. The results also is indicate influence positive leadership on the psychological capital in among teachers.The results also is indicate influence positive leadership on the psychological capital in among teachers.The results also is indicate influence positive leadership on the psychological capital in among teachers.